2016
DOI: 10.1002/adom.201600768
|View full text |Cite
|
Sign up to set email alerts
|

Visible Range Plasmonic Modes on Topological Insulator Nanostructures

Abstract: CommuniCationplasmon resonances in the entire visible spectrum by varying the partial ratio of the building elements in TI compounds, [9,13] bearing high potential for photonics applications. Recent studies revealed potential benefits of using TI visible range plasmons for light harvesting applications. [7,9] TIs form an intrinsic core-shell structure with metal-like surface state layer and insulating bulk, while its practical applications in optical or electronic devices require low residual conductivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 28 publications
1
68
0
Order By: Relevance
“…BSTs and BSTSs belong to the last generation of topological insulators which have attracted the attention of the scientific community in relation with their outstanding surface transport properties. The experimentally determined dielectric function of the Bi1.5Sb0.5Te1.8Se1.2 was reported by Ou et al [15], and Dubrovkin et al [65]. Yin et al [66] reported quantum simulated dielectric functions for several ternary and quaternary compounds: Bi2Se2Te, Bi2SeTe2, BiSbTeSe2, BiSbTe2Se.…”
Section: Ternary and Quaternary Compoundsmentioning
confidence: 78%
See 1 more Smart Citation
“…BSTs and BSTSs belong to the last generation of topological insulators which have attracted the attention of the scientific community in relation with their outstanding surface transport properties. The experimentally determined dielectric function of the Bi1.5Sb0.5Te1.8Se1.2 was reported by Ou et al [15], and Dubrovkin et al [65]. Yin et al [66] reported quantum simulated dielectric functions for several ternary and quaternary compounds: Bi2Se2Te, Bi2SeTe2, BiSbTeSe2, BiSbTe2Se.…”
Section: Ternary and Quaternary Compoundsmentioning
confidence: 78%
“…The optical and resonant properties of nanostructures based on V-VI topological insulators are since recently focusing the attention [15,65,[91][92][93][94][95][96]. Resonances Zhao et al [92] also demonstrated an active switching of these resonances upon crystalline to amorphous phase transition and discussed their potential for enhancing the performance of polymer solar cells.…”
Section: V-vi Topological Insulatorsmentioning
confidence: 99%
“…12,13 In addition, multiple plasmon modes were recently reported in solution-synthesized Bi 2 Te 3 nanoplates 14 and nano-discs and flakes of BSTS. 15 Ellipsometric data indicated the presence of high optical conductivities, possibly linked to the existence of topologically protected surface states. If true, BSTS or other TIs would be a radically new material platform for broadband nanoplasmonic devices that can be modulated optically, 16 through injection of electrons, 17 or by applied magnetic fields.…”
Section: Introductionmentioning
confidence: 98%
“…The pulse duration of mid-IR radiation is typically 40-200 fs, which is sufficient to gain access to timescales where electron-phonon, and electron-spin coupling have not yet brought the electronic system into thermal equilibrium [50]. In the visible range several interesting spectral features such as excitonic modes in transition metal dichalcogenides [61,62], plasmonic modes in metals and topological insulators [63], as well as resonances related to interband transitions in insulators, across charge transfer and Mott-Hubbard gaps can be observed. The pulse duration of visible radiation, which can be in the range of 4-40 fs, also enables indirect access to resonant modes in the infrared spectral range such as coherent phonons and Raman active modes [64,65].…”
Section: Outlook and Conclusionmentioning
confidence: 99%